Global burden of skin cancer and its subtypes: a comprehensive analysis from 1990 to 2021 with projections to 2040 - Chen, Keyue; Liu, Xiaoyi (Frontiers in Public Health, 2025)
BackgroundSkin cancer represents a significant global public health concern. Comprehensive analysis of its global burden provides critical insights for evidence-based interventions. This study systematically evaluates the global disease burden of skin cancer and its subtypes.MethodsThis study analyzed GBD 2021 data to assess ASIR and ASDR trends for total skin cancer and its subtypes (1990–2021), stratified by geography, age, and sex, using APC modeling, decomposition analysis, and inequality assessments, with projections through 2040.ResultsFirst, skin cancer ASIR increased from 1990 to 2021, while ASDR significantly decreased. Second, geographical heterogeneity existed in distribution of histological subtypes. Third, skin cancer burden demonstrated age-dependent progression with compositional variance in subtypes across age groups. Fourth, sex disparities intensified beyond age 55, with increasing longitudinal divergence. Fifth, both the ASIR and ASDR of total skin cancer showed non‑linear associations with SDI. Sixth, international disparities in skin cancer burden demonstrated a decreasing trend. Finally, projections to 2040 indicate a continued increase in total skin cancer ASIR accompanied by a persistent decline in total skin cancer ASDR.ConclusionASIRs of total skin cancer and its subtypes showed increasing trends, while ASDRs demonstrated decreasing patterns, with significant heterogeneity across regions, age groups, and sex.